Transfusion Medicine Made Easy For Students of Biomedical Science, Allied Medical Sciences and Medicine - Erhabor, Osaro; Charles Adias, Teddy (IntechOpen, 2012)
This basic text is intended to optimise the training and practice of transfusion medicine in developing countries particularly in sub- Saharan Africa. It is aimed at improving the knowledge and skills of allied medical and medical students, and other healthcare professionals involved in blood transfusion, empowering them to offer the best possible blood transfusion services to their patients. This book is suitable not only for allied medical and medical students preparing for their examination in transfusion medicine but also for postgraduates preparing for examination in general medicine, haematology and transfusion science. The chapters have been presented in an annotated and easy to understand format.